2016
DOI: 10.1063/1.4948991
|View full text |Cite
|
Sign up to set email alerts
|

The Weyl realizations of Lie algebras, and left–right duality

Abstract: Abstract. We investigate dual realizations of non-commutative spaces of Lie algebra type in terms of formal power series in the Weyl algebra. To each realization of a Lie algebra g we associate a star-product on the symmetric algebra S(g) and an ordering on the enveloping algebra U (g). Dual realizations of g are defined in terms of left-right duality of the star-products on S(g). It is shown that the dual realizations are related to an extension problem for g by shift operators whose action on U (g) describes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…K µ = k µ . Such a realization is called Weyl realization in the literature, see [45] and references therein. Furthermore, for Hermitian realizations of the Snyder-type spaces we have…”
Section: On the Snyder-type Realization With S1 = −S2mentioning
confidence: 99%
“…K µ = k µ . Such a realization is called Weyl realization in the literature, see [45] and references therein. Furthermore, for Hermitian realizations of the Snyder-type spaces we have…”
Section: On the Snyder-type Realization With S1 = −S2mentioning
confidence: 99%
“…[29] which states that the Weyl symmetric realization of a Lie algebra g 0 can be generalized to Lie superalgebras g = g 0 ⊕ g 1 satisfying [g 1 , g 1 ] = {0} where [· , ·] is the supercommutator in g. For details on the Weyl realization of g 0 see Refs. [30] and [31]. The evidence for this conjecture was found indirectly by using an automorphism of the Weyl superalgebra and comparing the power series expansion of two different realizations of g to second order in the structure constants of g. Here we give an elegant proof of this conjecture using the functional equation satisfied by the generating function for the Bernoulli numbers.…”
Section: Introductionmentioning
confidence: 84%
“…In Ref. [31] it was shown that the realization (20) can also be found by extending the original Lie algebra g 0 by n 2 generators T µν satisfying the Lie bracket [T µν , T αβ ] = 0 and [T µν , X λ ] = n α=1 C µλα T αν in order to derive the function f (t). Using an action of the Weyl algebra A n on the space of polynomials K[x 1 , .…”
Section: The Weyl Formula For Lie Algebrasmentioning
confidence: 99%
See 2 more Smart Citations